ANALISIS PENGARUH TINGKAT PEMBANGUNAN INFRASTRUKTUR TERHADAP ANGKA KEMISKINAN DI KABUPATEN PENUKAL ABAB LEMATANG ILIR - Amalindo, Heri; Saggaff, Anis; Juliana, Imroatul C; Ansyory, Deby (LATERAL: Jurnal Teknik Sipil, 2025)
In the era of globalization, regional improvements can be seen through infrastructure development which is one of the important and essential aspects to accelerate the development process of a country and region. The central and regional governments continue to expand infrastructure throughout Indonesia every year. Infrastructure not only concerns the development of the transportation sector such as the construction of roads and bridges, but also basic service facilities in other sectors such as the business world, education, and health. The problem of poverty can be overcome by having infrastructure that supports the local community which can be done in the form of cooperation between business entities, this is stated in Presidential Regulation of the Republic of Indonesia Number 38 of 2015. The purpose of the study was to analyze the effect of the development of road, health, education and clean water infrastructure on poverty rates using correlation analysis and multiple regression analysis. The data obtained came from the Central Statistics Agency of PALI Regency from 2019 - 2023. The data will be analyzed using a descriptive and quantitative approach, namely explaining the trends that occur. The results of the study showed that the variable that greatly influenced the poverty rate was the human development index (HDI) with a Pearson correlation of 0.970 and a multiple regression coefficient of 0.448.